Prevalence and Risk Factors of Taenia solium Infection among Humans and Pigs in Wukari Local Government Area, Taraba State, Nigeria - Ogbadu J. I; Agere H. I J; Benson O; Mijah A. K (Kwaghe International Journal of Sciences and Technology, 2026)
Taenia solium, the pork tapeworm, remains a major zoonotic parasite of public health and economic significance in many low- and middle-income countries, including Nigeria. The infection causes taeniasis in humans and cysticercosis in pigs, with transmission sustained by poor sanitation, free-range pig rearing, and inadequate meat inspection. This study determined the prevalence and risk factors associated with T. solium infection among pigs and humans in Wukari Local Government Area (LGA), Taraba State, Nigeria. A cross-sectional study was conducted between January and June 2024. Stool samples from 402 human participants and carcasses from 390 pigs were examined using standard parasitological and post-mortem inspection techniques. Socio-demographic and behavioral data were obtained through structured questionnaires. Data were analyzed using SPSS version 26.0, and associations between infection and risk factors were evaluated using Chi-square (χ²) and logistic regression at a significance level of p < 0.05. The overall prevalence of T. solium infection was 4.8% (38/792). Infection was detected in 4.9% of pigs and 4.7% of humans (χ² = 0.0387, p < 0.05). The highest prevalence among pigs occurred in Puje Ward (6.41%), while Hospital and Rafin Kada Wards recorded the highest human infection rates (5.97%). Significant risk factors identified included home slaughtering (OR = 2.1, 95% CI: 1.1–4.0), poor sanitation (OR = 1.8, 95% CI: 1.0–3.2), sale of infected pork (OR = 1.9, 95% CI: 1.1–3.3), and low public awareness (OR = 2.3, 95% CI: 1.2–4.4). The study reveals continued endemicity of T. solium in Wukari, driven by modifiable socio-behavioral factors. Strengthened meat inspection, improved sanitation, public education, and adoption of One Health surveillance strategies are recommended to reduce transmission and support Nigeria’s NTD elimination goals by 2030.